Behavior of Cosmic Rays and Propellant-Free Microwave Thruster Can Support the Hypothesis of Crystalline Vacuum - Lebedev, Sergey G. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
The paper suggests an explanation of the efficiency of the EmDrive device based on the hypothesis of a crystalline vacuum, previously successfully used to explain the cutoff of the cosmic-ray spectrum. The hypothesis of crystalline vacuum enables to transform part of momentum directly to vacuum crystalline lattice giving rise to reaction force which allow to ensure the fulfillment of the momentum conservation law during EmDrive functioning. Therefore crystalline vacuum plays the role of a supporting medium for all wave vectors of electromagnetic oscillations in a conical resonator, which causes the appearance of forces and momentums of rotation, the optimization of which can open up a tempting prospect for creating of unique aircraft.